2003
DOI: 10.1103/physrevb.68.085413
|View full text |Cite
|
Sign up to set email alerts
|

Dephasing of electrons in mesoscopic metal wires

Abstract: We have extracted the phase coherence time τ φ of electronic quasiparticles from the low field magnetoresistance of weakly disordered wires made of silver, copper and gold. In samples fabricated using our purest silver and gold sources, τ φ increases as T −2/3 when the temperature T is reduced, as predicted by the theory of electron-electron interactions in diffusive wires. In contrast, samples made of a silver source material of lesser purity or of copper exhibit an apparent saturation of τ φ starting between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
295
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(319 citation statements)
references
References 43 publications
(76 reference statements)
23
295
1
Order By: Relevance
“…For W ≥ 3.5 × 10 −10 W the response becomes non-linear. The measured responsivities agree within 10% to the predicted disconnected thermal model responsivities with literature [12,13], and fit values. The measured responsivities only agree within 50% to the ideal model.…”
Section: Responsivity Measurementssupporting
confidence: 64%
See 1 more Smart Citation
“…For W ≥ 3.5 × 10 −10 W the response becomes non-linear. The measured responsivities agree within 10% to the predicted disconnected thermal model responsivities with literature [12,13], and fit values. The measured responsivities only agree within 50% to the ideal model.…”
Section: Responsivity Measurementssupporting
confidence: 64%
“…The fitted e-p values and conductances for both models are listed in Table 1. The disconnected model fits to values only slightly lower than literature values [12,13]. In all cases the ep conductance is substantially greater than the e-e conductance along the absorber, further supporting a disconnected model for this test device.…”
Section: W Vs T Bath and Thermal Conductance Measurementssupporting
confidence: 50%
“…This constructive interference can, however, be reduced by applying an external magnetic field, so the measured electrical resistance is a maximum at zero applied field and falls to the classical resistance value as the magnetic field is increased-a hallmark of weak localization. Weak localization also has a very characteristic temperature dependence, as elevating the temperature increases the inelastic scattering rate, thereby suppressing the constructive interference and reducing the weak localization resistance peak 15,16 . Given that quantum interference lies at the heart of weak localization, it is natural to use wave-like systems to emulate this effect.…”
mentioning
confidence: 99%
“…13 . The situation here is to be contrasted with the absence of spin disorder, where it has been shown that…”
mentioning
confidence: 99%
“…Decoherence arises from coulombic interactions, scattering by phonons, magnetic fluctuations etc. The saturation of the dephasing rate at low temperature T seen in numerous experiments [1][2][3][4][5][6][7][8][9][10][11][12][13] has attracted a vigorous interest, especially given the longstanding theoretical prediction for a vanishing τ −1 φ as the temperature T → 0. [14][15][16][17][18][19][20][21] .…”
mentioning
confidence: 99%